2018
DOI: 10.1080/13696998.2018.1490301
|View full text |Cite
|
Sign up to set email alerts
|

Cost estimate of platelet transfusion in the United States for patients with chronic liver disease and associated thrombocytopenia undergoing elective procedures

Abstract: Although we were unable to include all cost components identified in the conceptual framework in our total cost estimate, thus likely underestimating the true total cost, and despite the data gaps and challenges limiting our estimate of the full cost of a platelet transfusion in patients with CLD-associated thrombocytopenia undergoing an elective procedure in the United States, this study outlines a comprehensive conceptual framework for estimating the cost elements of a platelet transfusion in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…The results of the one-way sensitivity analysis suggest that further research into the full cost of platelet transfusion could affect the findings from this analysis. Although Barnett et al (2018) 7 detailed the cost of a platelet transfusion in the US, there is a lack of information crucial to understanding the full cost of a platelet transfusion, as the authors noted data gaps in the literature. Since not all costs could be accounted for in the cost estimate from that study, the platelet transfusion cost used here may be an underestimate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the one-way sensitivity analysis suggest that further research into the full cost of platelet transfusion could affect the findings from this analysis. Although Barnett et al (2018) 7 detailed the cost of a platelet transfusion in the US, there is a lack of information crucial to understanding the full cost of a platelet transfusion, as the authors noted data gaps in the literature. Since not all costs could be accounted for in the cost estimate from that study, the platelet transfusion cost used here may be an underestimate.…”
Section: Discussionmentioning
confidence: 99%
“… 6 The increased risk of bleeding complications is often managed with preoperative platelet transfusion; 6 however, this treatment often does not adequately address the therapeutic need and is associated with substantial risk of allergic reactions, reduced efficacy over time, costs, and potential adverse effects. 7 Given the limitations with current standard of care, there is a need for a safe and cost-effective alternative treatment for thrombocytopenia in patients with CLD who are preparing for a procedure.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the total cost (which includes the cost of generating supply of platelets, cost of adverse events and refractoriness to platelet transfusions) of administration of platelet transfusions among patients with CLD estimated that platelet transfusions can cost between $5258 to $13 117. 24 A study on the increased resource utilisation and costs associated with management of thrombocytopaenia in this population found that CLD patients with thrombocytopaenia incurred $43 562 in annual medical costs, compared to $12 271 among CLD patients without thrombocytopaenia. 25 A similar study on the increased resource utilisation and costs associated with management of thrombocytopaenia among patients with hepatitis C viral (HCV) indicated that HCV patients with thrombocytopaenia incur an estimated $37 924 in annual healthcare costs, compared to $12 174 among HCV patients who do not have thrombocytopaenia.…”
Section: Introductionmentioning
confidence: 94%
“…Prior studies have reported the economic burden associated with thrombocytopaenia and platelet transfusions among patients with CLD. A study of the total cost (which includes the cost of generating supply of platelets, cost of adverse events and refractoriness to platelet transfusions) of administration of platelet transfusions among patients with CLD estimated that platelet transfusions can cost between $5258 to $13 117 . A study on the increased resource utilisation and costs associated with management of thrombocytopaenia in this population found that CLD patients with thrombocytopaenia incurred $43 562 in annual medical costs, compared to $12 271 among CLD patients without thrombocytopaenia .…”
Section: Introductionmentioning
confidence: 99%
“…Across publications reporting PT costs in CLD patients, the reported estimated cost for 1-2 PTs ranged from $500 [138] to $1639 [69], while the total estimated costs of PT were reported as $5258-13,117 in 1 publication and $4800-11,000 in another [134,138].…”
Section: Economic Burdenmentioning
confidence: 99%